PENGARUH PROGRAM MATA NAJWA MELALUI MEDIA SOSIAL TERHADAP SIKAP POLITIK REMAJA DI DESA SEPANJANG KECAMTAN GLENMORE KABUPATEN BANYUWANGI - tulloh, ferdian rohmad; suyono (MEDIAKOM, 2024)
Abstract This study aims to evaluate the influence of the Mata Najwa program through social media on the political attitudes of adolescents in Sepanjang Village, Glenmore District, Banyuwangi Regency. The rapid development of information anditechnology, especially through social media, has opened up space for political participation for teenagers. This quantitative research aim to examine the nfluence of the Mata Najwa program on social media on adolescents' political attitudes, based on the Uses and Effect Theory. The results of a study in Sepanjang Village, Banyuwangi, show that the "Mata Najwa" program has a positive and significant influence on the political attitudes of adolescents. Statistical analysis yielded a calculated t value (7,306) that was greate than the t table (1,989) with a significance of 0.00<0.05, so that null hypothesis was rejected. The RSquare value of0.37 indicates that the 37% variability of adolescents' political attitudes can be explained by the Mata Najwa program. This study concludes that the Mata Najwa program through social media has a moderate but significan influence on the formation of adolescent political attitudes.   Keywords: Political Attitudes, Social Media, Mata Najwa, Use and Effect.